FAMILY AND PROFESSIONAL LIFE OF PUBLIC ADMINISTRATION EMPLOYEES. A SOCIOLOGICAL DIAGNOSIS 2015 - Kawińska, Martyna (Uniwersyteckie Czasopismo Socjologiczne, 2016)
In 2015, a research team of the Polish Measurement of Attitudes and Values carried out a representative survey of public administration employees. There were 746 survey participants who represented public administration entities from 16 voivodships in Poland, varied in terms of the most important sociodemographic features. The data were collected by means of the CAWI technique in the variant of direct contact with the respondent, with the computer record of responses in the form of an electronic self-returnable questionnaire.